Pengembangan Bahan Ajar IPS Dinamika Interaksi Sosial di Dalam dan Luar Sekolah bagi Siswa Kelas V MI Mambul Ulum Tarik Sidoarjo - Inayatu Khoirul Magfiroh (ENTITA: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2021)
This research is aimed at developing teaching materials in the form of social studies modules on the dynamics of social interaction inside and outside the Sidoarjo school. The objectives to be achieved are: (1) the preparation of the MI IPS module for class V students in the second semester of MI, (2) the identification of the effectiveness of the MI IPS module on student learning outcomes. This research was carried out through nine stages, namely (1) identifying the general objectives of teaching, (2) carrying out learning analysis, (3) identifying initial input behavior and student characteristics, (4) formulating performance goals, (5) developing test items. benchmark reference, (6) developing teaching strategies, (7) developing and selecting learning materials, (8) designing and implementing formative evaluations, (9) revising learning materials, (9) designing and implementing summative evaluations. Adapted from the Dick and Carey model. The data from the module validation results are obtained as follows: Responses from the validation expert (1) The material quality component on the material suitability criteria has an average score of 3.0 with a good category, on the material shortage criteria has an average score of 3.5 with a good category, while the criteria for learning support materials have an average score of 3.0 with a good category. (2) the linguistic quality component on the criteria for conformity with the level of development of students has an average score of 4.0 with a very good category, on the communicative criteria has an average score of 3.0 with a good category, while the criteria for coherence and integration of the flow of thought has an average score of 3.0 with a good category. (3) the presentation quality component on the presentation technique criteria has an average score of 3.6 with a very good category, while the learning presentation criteria has an average score of 3.5 with a good category. And the criteria for the completeness of the presentation have an average score of 3.3 with a good category. From the results of mastery learning, students using the module get a calculation of the average score for the pre-test is 72, while the average score for the post-test is 80. Based on the results of data analysis, it can be concluded that the development of teaching materials for the dynamics of social interaction with the resulting product is Modules in Social Studies MI learning obtained module quality and effectiveness to improve mastery learning outcomes, but still require adjustment to the situation and conditions at school.